Engineering Vibrio alginolyticus as a novel chassis for PHB production from starch - Li, Hong-Fei; Tian, Linyue; Lian, Guoli; Fan, Li-Hai; Li, Zheng-Jun (Frontiers in Bioengineering and Biotechnology, 2023)
Vibrio alginolyticus LHF01 was engineered to efficiently produce poly-3-hydroxybutyrate (PHB) from starch in this study. Firstly, the ability of V. alginolyticus LHF01 to directly accumulate PHB using soluble starch as the carbon source was explored, and the highest PHB titer of 2.06 g/L was obtained in 18 h shake flask cultivation. Then, with the analysis of genomic information of V. alginolyticus LHF01, the PHB synthesis operon and amylase genes were identified. Subsequently, the effects of overexpressing PHB synthesis operon and amylase on PHB production were studied. Especially, with the co-expression of PHB synthesis operon and amylase, the starch consumption rate was improved and the PHB titer was more than doubled. The addition of 20 g/L insoluble corn starch could be exhausted in 6-7 h cultivation, and the PHB titer was 4.32 g/L. To the best of our knowledge, V. alginolyticus was firstly engineered to produce PHB with the direct utilization of starch, and this stain can be considered as a novel host to produce PHB using starch as the raw material.